ZONASI ANTARA STASIUN PENGISIAN BAHAN BAKAR UMUM (SPBU) DENGAN PERMUKIMAN PENDUDUK DITINJAU DARI HUKUM TATA RUANG DI SAMARINDA - Risna Wati (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT This study aims to determine the stages, terms and conditions that must be done in the development process of a General Fuel Filling Station (gas stations) in Samarinda and to determine what sanctions can be awarded against violations of the applicable provisions of the development and activities of Charging Stations General Fuel (gas stations) in Samarinda. This research was conducted by the sociological juridical approach that examines the legislation and the fact that there are seen from the perspective of law enforcement.Based on the research that has been done, it is known the terms, conditions and process of the establishment of a General Fuel Filling stations (gas stations) in Samarinda, namely 1) Register online on the official website of PT. Pertamina, which stages include inputting location data and account activation, employer profiles, company profiles and layouts. 2) Verify the initial form of the selection of financial preparedness and readiness of selection of land. 3) Verify field to synchronize the data that has been disikan with the fact the field. 4) Approval of the business feasibility of the PT. Pertamina then prospective partners are asked to complete the application for a new permit requirements General Fuel Filling Station (Gas Station). The four stages that must be done before building General Fuel Filling Station (Gas Station) with a construction period that has been determined by the PT. Petamina. Given legal effect when the building General Fuel Filling Station (Gas Station) is not in accordance with the provisions of Samarinda City Regional Regulation No. 34 of 2004 on Building In Samarinda City area may be liable to criminal sanctions (imprisonment or fines) and administrative sanctions, and based Samarinda City Regional Regulation No. 11 Year 2014 on the Implementation of Exertion or Oil and Gas Activities can be subject to administrative sanctions.From this conclusion, the authors suggest to the government of Samarinda to be more careful in the process of verifying the licensing General Fuel Filling Station (Gas Station) with more attention to the existing terms and conditions in accordance with the legislation in force and to maximize the application of rules and appropriate sanctions with the legislation in force. Keyword : zonation, SPBU.